Noviana, Sari PENGARUH PENUTUPAN LOKALISASI DOLLY DAN JARAK TERHADAP AKTIVITAS EKONOMI WARGA SEKITAR (JBT (JURNAL BISNIS dan TEKNOLOGI), 2015)
Dolly Localization that closed by Surabaya city Goverment became sensational news , but because of the resistance efforts of the prostitutes and pimps , also because of the economic impact of society in the region. With a variety of preparations and potential, Surabaya city Goverment finally managed to close the localization which is very famous and is considered as the biggest prostitution in Southeast Asia . Closure Dolly is a dilemma . On the one hand prostitution contrary to religious teachings and may even adversely affect the mental development of children in the vicinity, while on the other hand there are economic problems that need to be helped to look for the best solution